Effects of Intestinal FXR-Related Molecules on Intestinal Mucosal Barriers in Biliary Tract Obstruction - Yan, Meng; Hou, Li; Cai, Yaoyao; Wang, Hanfei; Ma, Yujun; Geng, Qiming; Jiang, Weiwei; Tang, Weibing (Frontiers in Pharmacology, 2022)
Background: The farnesoid X receptor (FXR) is a key factor regulating hepatic bile acid synthesis and enterohepatic circulation. Repression of bile acid synthesis by the FXR is a potential strategy for treating cholestatic liver disease. However, the role of intestinal FXR on the intestinal barrier and intestinal microbiota needs further investigation. This study determined the role of the FXR pathway in protecting the intestinal barrier and composition of the intestinal microbiota in obstructive jaundice. Materials: Intestinal tissues were collected from patients with biliary atresia. Then, intestinal mRNA levels of FXR-related molecules were determined. After undergoing bile duct ligation (BDL), rats were treated with obeticholic acid (OCA [5 mg/kg/day]) per oral gavage for 14 days. First, the intestinal Fxr, Shp, TNF-α, and Fgf15 levels were determined. In addition, the intestinal permeability, morphologic changes, and composition of the intestinal microbiota were evaluated. Finally, the role of OCA in injured intestinal epithelial cell apoptosis was examined by pretreatment with lipopolysaccharide (LPS) in Caco-2 cells. Results: Expression of the FXR in intestinal tissues was significantly increased in humans, while the expression of downstream SHP and FGF19 was significantly decreased. Thus, the signal pathway downstream of the FXR in intestinal tissue was inhibited in biliary obstruction. Activation of the FXR signaling pathway by OCA significantly reduced liver fibrosis and intestinal inflammation, improved intestinal microbiota, and protected intestinal mucosa in a rat model of BDL. Moreover, OCA reduced the apoptosis induced by LPS in Caco-2 cells. Conclusion: The FXR agonist, OCA, activated the intestinal FXR signaling pathway and improved the composition and structure of the intestinal microbiota and intestinal barrier in BDL rats.